Board gender diversity and carbon proactivity: The influence of cultural factors - Haifei Wang; Qingliang Tang; Ting Guo (Journal of Risk and Financial Management, 2023)
Due to inadequate studies, our knowledge of the effect of female directors and national culture on the corporate response to climate change is still limited. To address this gap, the purpose of this paper is to investigate the dynamic relationship between gender diversity on the board of directors and corporate carbon proactivity and how two dimensions of national culture (individualism and indulgence) moderate this relationship. This study focuses on large companies that disclosed carbon-related information via the CDP survey in 2011-2017. Our findings show that gender diversity promotes corporate carbon proactivity. Furthermore, the positive effect of gender diversity on carbon proactivity is weaker when firms are in countries marked by a higher level of individualism and indulgence. As far as we know, this study is the first to explore and document the empirical evidence on the dynamic impact of gender diversity in the corporate governance body and national culture on managers' climate change behaviors in terms of green proactivity.
Keywords: 650; board gender diversity; carbon proactivity; climate change; individualism; indulgence